Analisis Perbedaan Return Saham, Abnormal Return, Harga Saham, dan Volume Perdagangan Saham di Masa Pandemi Covid-19: Studi Kasus pada Perusahaan Sektor Industri Transportasi yang Terdaftar di Bursa Efek Indonesia Periode 2019-2022 - Dela Puspita Mantulangi; Mohamad Agus Salim Monoarfa; Meriyana Franssisca Dungga (Masyarakat Ekonomi Syariah Bogor, 2024)
This study aimed to determine any significant difference between stock returns , abnormal returns , stock prices , and stock trading volumes before and after the COVID - 19 pandemic in transportation sector companies listed on the Indonesia Stock Exchange . This research used secondary data with descriptive analysis and quantitative analysis methods . Data analysis in this study used the Wilcoxon signed - rank test , and the data for this study were collected two years before ( 2019-2020 ) and two years after ( 2021-2022 ) the COVID - 19 pandemic in Indonesia . The results show no significant difference in stock returns and stock prices . However , there is a significant difference in abnormal returns and stock trading volumes before and after the COVID -